Vinegar Consumption Increases Insulin-Stimulated Glucose Uptake by the Forearm Muscle in Humans with Type 2 Diabetes. (6th May 2015) - Mitrou, Panayota; Petsiou, Eleni; Papakonstantinou, Emilia; Maratou, Eirini; Lambadiari, Vaia; Dimitriadis, Panayiotis; Spanoudi, Filio; Raptis, Sotirios A.; Dimitriadis, George
Abstract : Background and Aims . Vinegar has been shown to have a glucose-lowering effect in patients with glucose abnormalities. However, the mechanisms of this effect are still obscure. The aim of this randomised, crossover study was to investigate the effect of vinegar on glucose metabolism in muscle which is the most important tissue for insulin-stimulated glucose disposal. Materials and Methods . Eleven subjects with DM2 consumed vinegar or placebo (at random order on two separate days, a week apart), before a mixed meal. Plasma glucose, insulin, triglycerides, nonesterified fatty acids (NEFA), and glycerol were measured preprandially and at 30–60 min for 300 min postprandially from the radial artery and from a forearm vein. Muscle blood flow was measured with strain-gauge plethysmography. Glucose uptake was calculated as the arteriovenous difference of glucose multiplied by blood flow. Results . Vinegar compared to placebo (1) increased forearm glucose uptake( p = 0.0357 ), (2) decreased plasma glucose (p = 0.0279 ), insulin( p = 0.0457 ), and triglycerides( p = 0.0439 ), and (3) did not change NEFA and glycerol. Conclusions . In DM2 vinegar reduces postprandial hyperglycaemia, hyperinsulinaemia, and hypertriglyceridaemia without affecting lipolysis. Vinegar's effect on carbohydrate metabolism may be partly accounted for by an increase in glucose uptake, demonstrating an improvement in insulin action in skeletal muscle. This trial is registered with Clinicaltrials.govNCT02309424 .